An insight into the global market penetration by a Malaysian construction firm – evaluation of the construction industry in international markets / Noraliza Basrah - Basrah, Noraliza (Kolej Cempaka Kenanga, UiTM Shah Alam, 2000)
This paper is prepared during the study of MSc. in Integrated Construction Project Management (August 1999) to fulfil the requirements for the subject of "Evaluation of Construction Industry in International Markets". It is developed upon an investigation of a construction firm which has ventured into the global market. The underlying questions are focused towards the firm's strategic encounter abroad. It is hoped that the summary content of the subject coursework may provide readers with some critical points towards facing the global impact within an industry. It includes the premise of study, an introduction to the firm studied, highlights of its critical success factors and strategic encounter abroad. The author finally outlines the findings into a set of resources being used by the firm for their own competitive advantages.